Peran Estetika dalam Drama: Pengaruh Gaya Bahasa dan Alur terhadap Pengembangan Cerita dalam Naskah Drama Sumur Tanpa Dasar Karya Arifin C. Noer - Nur Azila; Nur’almaydaniati Hamid; Putri Rahmadani; Rahmatul Jannah; Renita Hastuti; Herlinda Herlinda (Universitas Palangka Raya, 2025)
This study aims to analyze the role of aesthetics in the drama Sumur Tanpa Dasar by Arifin C. Noer, focusing on the influence of language style and plot on story development. Using a qualitative approach and textual analysis, this research explores how language style shapes character development and expresses inner conflict, while the non-linear plot creates dynamic tension and dramatic conflict. The findings reveal that each character’s distinctive language style enhances characterization and reflects their psychological conditions. Meanwhile, the non-linear plot allows for deeper exploration of conflicts and offers a complex aesthetic experience for the audience.